Unveiling the Gating Mechanism of CRAC Channel: A Computational Study - Guardiani, Carlo; Sun, Delia; Giacomello, Alberto (Frontiers in Molecular Biosciences, 2021)
CRAC channel is ubiquitous and its importance in the regulation of the immune system is testified by the severe immunodeficiencies caused by its mutations. In this work we took advantage on the availability of open and closed structures to run for the first time simulations of the whole gating process reaching the relevant time-scale with an enhanced sampling technique, Targeted Molecular Dynamics. Our simulations highlighted a complex allosteric propagation of the conformational change from peripheral helices where the activator STIM1 binds, to the central pore helices. In agreement with mutagenesis data, our simulations revealed the key role of H206 whose displacement creates an empty space behind the hydrophobic region of the pore, thus releasing a steric brake and allowing the opening of the channel. Conversely, the process of pore closing culminates with the formation of a bubble that occludes the pore even in the absence of steric block. This mechanism, known as "hydrophobic gating", has been observed in an increasing number of biological ion channels and also in artificial nanopores. Our study therefore will not only contribute to the treatment of diseases caused by disrupted calcium signaling, but it will help to clarify the mode of action of hydrophobically gated ion channels, possibly even suggesting strategies for the biomimetic design of synthetic nanopores.